Hubungan Supervisi Akademik Kepala Sekolah dan Gaya Kepemimpinan Kepala Sekolah dengan Kinerja Guru SMA Negeri di Kecamatan Bula dan Bula Barat Kabupaten Seram Bagian Timur - Luturlean, Sofyan; Wenno, I.H.; Lekatopessy, J. E. (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to: 1) describe the academic supervision of public high school principals in Bula and West Bula sub-districts, Eastern Seram District, 2) describe the leadership style of public high school principals in Bula and West Bula Districts, East Seram District, 3) describe about the performance of public high school teachers in Bula and West Bula sub-districts, 4) to find out the relationship between the academic supervision of school principals and the performance of public high school teachers in Bula and West Bula sub-districts, East Seram Regency, 5) to find out the relationship between the principal's leadership style and performance public high school teachers in Bula and West Bula Districts, East Seram District. And 6) to find out the relationship between the principal's academic supervision and the principal's leadership style together with the performance of public high school teachers in Bula and West Bula Districts, East Seram District. The population in this study were all teachers at SMA Negeri 1 Seram Timur, totaling 56 teachers. The results of the study show that there is a positive and significant relationship between Principal Academic Supervision and Teacher Performance with a correlation value of 0.337 and a significance value of 0.011. There is a positive and significant relationship between the Principal's Leadership Style and Teacher Performance with a correlation value of 0.354 and a significance value of 0.007. There is a positive and significant relationship between the Principal's Academic Supervision and the Principal's Leadership Style together on Teacher Performance with a correlation value of 0.427 and a significance value of 0.005.